092 Interstitial expansion in health and disease—an equilibrium contrast CMR study. (16th May 2012) - Sado, D M; Flett, A S; Banypersad, S; White, S; Hughes, D; Mehta, A; Murphy, E; Lachmann, R; Hawkins, P; Hausenloy, D; McKenna, W; Taylor, A; et al.
Abstract : Introduction: Interstitial myocardial volume expansion is an important factor in cardiac disease but until recently could only be accurately assessed with myocardial biopsy. It is usually a result of diffuse fibrosis, but can also be caused by infiltration (such as by amyloid deposition) or oedema. We have used a new method, Equilibrium Contrast Cardiovascular Magnetic Resonance (EQ-CMR) to accurately quantify the interstitial space in normal subjects and across a broad spectrum of cardiac diseases. Methods: The three steps in EQ-CMR are: (1) a primed gadolinium infusion to achieve contrast equilibrium, (2) Signal (T1) measurement pre and post equilibrium, (3) measurement of blood contrast volume (1−haematocrit). This allows calculation of the contrast volume of distribution, Vd(m), by: Vd ( m ) = ( 1 − haematocrit ) × Δ ( 1 / T1 ) myo ÷ Δ ( 1 / T1 ) blood . Vd(m) was measured in 278 subjects: 86 normal subjects (median age 43, range 24–81, 51% male) and 192 patients with Anderson-Fabry disease (AFD, n=17), dilated cardiomyopathy (DCM, n=31), hypertrophic cardiomyopathy (HCM, n=31), severe aortic stenosis (AS, n=66), cardiac AL amyloidosis (n=27) or myocardial infarction (MI, n=20). Results: In normal subjects, mean Vd(m) was higher in females (0.274) than males (0.237, p<0.001). In all diseases, Vd(m) was higher than normal subjects (p<0.001) except the intracellular storage disease AFD (0.250, p=0.9). Vd(m) was the same in DCM (0.280), HCM (0.291) and AS (0.276), but higher in the exemplar of infiltrative disease, cardiac AL amyloidosis (0.466) and higher again in MI (0.585, each p<0.001), Abstract 092 figure 1 . These trends were also present when disease data were compared to gender matched normal subjects. Where Vd(m) was elevated, correlations existed with important clinical CMR parameters including ejection fraction, indexed left ventricular mass, end systolic volume and left atrial area, in apparent disease specific patterns, Abstract 092 table 1 . Conclusions: This study shows the ability of EQ-CMR to non-invasively quantify interstitial expansion using this novel technique in both the healthy population and a spectrum of differing cardiac diseases. Further work will build on this study to evaluate the potential role of Vd(m) as a clinical biomarker.